2000
DOI: 10.1080/000163500429424
|View full text |Cite
|
Sign up to set email alerts
|

In vitro shear bond strength of orthodontic bondings without liquid resin

Abstract: This study aimed at evaluating the early shear bond strength of enamel-composite-bracket adhesion accomplished without the use of liquid resin. Orthodontic brackets were bonded to the buccal surfaces of healthy extracted premolars in the test group by Transbond XT (n = 8) and Phase II (n = 8) composites but not the enclosed liquid resins in these products. Brackets bonded with the same materials (n = 8 for each) along with their corresponding liquid resin served as controls. The specimens were tested for shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
2
9
0
2
Order By: Relevance
“…The average shear strength of all composites tested in this study were >6 MPa, considered by Reynolds and Von Frauhofer [39] and others to be appropriate for routine clinical use. Mean values of shear strength were similar to previous studies [40,41] and were within the clinically acceptable bond strength range. However, in this study, the Transbond XT and Filtek Z100 composites showed the highest bond shear strength.…”
Section: Discussionsupporting
confidence: 86%
“…The average shear strength of all composites tested in this study were >6 MPa, considered by Reynolds and Von Frauhofer [39] and others to be appropriate for routine clinical use. Mean values of shear strength were similar to previous studies [40,41] and were within the clinically acceptable bond strength range. However, in this study, the Transbond XT and Filtek Z100 composites showed the highest bond shear strength.…”
Section: Discussionsupporting
confidence: 86%
“…It has often been described that the point of vulnerability in adhesive bonds is at the transition between the bracket and adhesive, which is why this is usually where the fracture occurs in shear tests [4,12,24]. Other studies, however, report less uniform distribution [2,3,17,20,29] or no correlation between shear bond strength and type of fracture [16]. In our study, we evaluated ARI scores in reference to microphotographs so that even miniscule amounts of adhesive residue or enamel fractures were detectable.…”
Section: Diskussionmentioning
confidence: 99%
“…Andere Studien wiesen jedoch eine weniger einheitliche Verteilung auf [2,3,17,20,29] oder zeigten keinen Zusammenhang zwischen Scherhaftfestigkeit und Bruchmodus [16]. In der vorliegenden Studie erfolgte die Auswertung des ARI-Grades anhand von mit dem Mikroskop erstellten Fotografien, damit auch geringe Adhäsivreste oder Schmelzausrisse erkennbar wurden.…”
Section: Diskussionunclassified
“…After bias risk analysis (Table 1), one study 11 was excluded due to its high risk of bias. Nine studies 2,3,8,[12][13][14][15][16][17] were included; descriptive data, random-effect means, confidence interval, and weight of each study are shown in Table 2. The lowest mean for bond strength in a group was 6.42 MPa; the highest value was 34.8 MPa, with 50% of the groups' means being lower than 11.0 MPa.…”
Section: Resultsmentioning
confidence: 99%